Musculoskeletal concerns do not justify failure to use safer sequential trigger to prevent acute nail gun injuries. Issue 4 (4th March 2015) - Lipscomb, Hester J.; Nolan, James; Patterson, Dennis
Abstract: Background: Acute nail gun injuries can be controlled significantly by using tools with sequential triggers and training. Concern has been raised that sequential triggers, which require that the nose piece of the gun be depressed prior to pulling the trigger, could increase risk of musculoskeletal problems. Methods: We conducted active injury surveillance among union carpenter apprentices to monitor acute injuries and musculoskeletal disorders between 2010 and 2013. Results: Acute injury risk was 70% higher with contact trip rather than sequential triggers. Musculoskeletal risk was comparable (contact trip 0.09/10, 000 hr (95% CI, 0.02–0.26); sequential 0.08/ 10, 000 hr (95% CI 0.02–0.23)). Conclusions: Concern about excess risk of musculoskeletal problems from nail guns with sequential triggers is unwarranted. Both actuation systems carry comparable musculoskeletal risk which is far less than the risk of acute injury; there is clearly no justification for failure to prevent acute injuries through use of the safer sequential trigger. Am. J. Ind. Med. 58:422–427, 2015. © 2015 Wiley Periodicals, Inc.